FROM BRIEF TO LUNCH: A PROJECT MANAGER’S GUIDE TO FLAWLESS MARKETING CAMPAIGN EXECUTION - Edy Sunarno; Lukmanul Hakim; Tibrani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing complexity of modern marketing campaigns has created a growing need for structured and efficient execution processes. Campaigns now span multiple channels, involve diverse stakeholders, and operate under tight timelines, making coordination and alignment critical for success. This article presents a practical guide for managing marketing campaigns from brief to launch by integrating project management principles with marketing practices. Using a conceptual and best-practice synthesis approach, the study draws on industry insights, case examples, and established project management frameworks to develop a structured execution model. The proposed framework outlines key phases, including campaign brief development, planning and strategy, team coordination, and content creation. The findings highlight that clear objectives, stakeholder alignment, and structured workflows are essential for reducing delays and inefficiencies. Additionally, effective communication and cross-functional collaboration play a crucial role in ensuring smooth execution. The study also emphasizes the importance of balancing planning structure with resource efficiency and combining role clarity with communication workflows. Overall, the article demonstrates that disciplined project management enhances campaign performance and consistency. It concludes that organizations adopting structured execution frameworks can improve efficiency, reduce risks, and deliver more impactful marketing outcomes.